PEMBUATAN E-LIBRARY DI BALAI BAHASA PROVINSI ACEH DENGAN MENGGUNAKAN PHP DAN MYSQL - Sahruddin (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2020)
So far, the existing book data information system at the Aceh Provincial Language Center still uses the manual method. The large number of printed manuscripts that entered and the transaction processes caused many difficulties in controlling books. In addition, data processing also takes a long time. From the background description, the authors define the problem only on how the E-library Database Management System at the Aceh Province Language Center Office and designing the E-library Database Management System at the Aceh Province Language Hall Office based on the web. The purpose of the discussion is to find out the E-library Database Management System at the Aceh Province Language Center Office and to design a web-based E-library Database Management System at the Aceh Province Language Center Office. For the perfection of this report, the authors collected data using several data collection methods, including using field studies and literature studies. The E-library Database Management System makes it easy for the Aceh Province Language Center Office to evaluate the handling of e-libraries, and this application, can overcome problems that exist at the Aceh Province Language Center Office because it speeds up reporting and reduces human errors.